Beyond Entrepreneurial Intention: A Social Capital-Based Conceptual Framework for the Economic Empowerment of University Student Entrepreneurs - Razali, Nur Azah; Kamri, Khairol Anuar; Razali, Asbah; Mohd Ali, Adi Syahid; Nik Nazli, Nik Nadian Nisa (Journal of Techno-Social, 2026)
Graduate unemployment and underemployment have intensified universities' responsibility to prepare students not only to seek jobs but also to create sustainable economic opportunities. Although much scholarship on student entrepreneurship has examined entrepreneurial intention, less attention has been given to the social and relational processes through which student-led ventures translate entrepreneurial activity into economic empowerment. This conceptual paper addresses this gap by developing a social capital-based framework for the economic empowerment of university student entrepreneurs. Using a narrative conceptual review, the paper synthesises literature on economic empowerment, student entrepreneurship, Social Capital Theory, entrepreneurial self-efficacy, and university entrepreneurial support. The framework conceptualises economic empowerment through income generation, financial autonomy, asset accumulation, and economic decision-making control. It proposes that structural, relational, and cognitive social capital enhance students' access to information, trust, legitimacy, shared entrepreneurial meanings, and venture resources. Entrepreneurial self-efficacy is positioned as a mediating mechanism through which social capital is converted into empowered entrepreneurial action, while university entrepreneurial support is framed as a moderating condition that strengthens the self-efficacy-empowerment relationship. The paper contributes to higher education and entrepreneurship scholarship by moving beyond intention-based explanations and offering a process-oriented model for understanding why some student entrepreneurs achieve economic empowerment. Practically, it provides universities with guidance for designing entrepreneurial programmes that intentionally build, activate, and sustain students' social capital.